ESP STUDENTS’ NEEDS ANALYSIS BASED ON THE LEARNING-CENTRED APPROACHED - Way Warti (LPPM Universitas Bina Sarana Informatika, 2020)
AbstractEnglish for Specific Purposes, known as ESP, has been a requirement in the field of English Language Teaching ,especially in the vocational college level. This case study aims at investigating the ESP language needs of students at Politeknik Tonggak Equator in Pontianak. The need analysis was based on the Hutchinson & Waters model, The Learning-Centered Approach Model, which is classified into two: target situation needs and learning needs. This study focused on the target need that includes “necessities”, “lacks” and “wants”aspects. Interviews to infer information for qualitative analysis were conducted with 10 students at the sixth semester of English Business and Management program. The findings revealed that students who were working at various companies confirmed that their necessities was to learn a much better skilled english to support their works. In term of lacks, some learners admitted that they had to improve their communication skills and the wants were to be able to communicate in the form of speaking and writing. Keywords : ESP, need analysis, the learning centred approach